The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1097/00008480-200108000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of thyroid development

Abstract: Normal thyroid function is essential for development, growth, and metabolic homeostasis. The prerequisites for an euthyroid metabolic state include a normally developed thyroid gland, a properly functioning system for thyroid hormone synthesis, and sufficient iodine intake. Defects in any of the essential steps in thyroid development or thyroid hormone synthesis may result in morphologic abnormalities and impaired hormonogenesis. These defects can be partial or complete, leading to varying degrees of hypothyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 23 publications
0
29
0
3
Order By: Relevance
“…The need for thyroid hormone at and after birth is well established: routine neonatal screening can identify infants with thyroid deficiencies, and very importantly this information allows treatment with replacement hormone in time to reduce subsequent neurological impairment. In countries with the resources for comprehensive screening, congenital hypothyroidism is detected in about 1 in 3500 newborns (1). Studies in animal models have identified a number of cellular migration and differentiation events in the postnatal brain that depend upon thyroid hormone (2).…”
mentioning
confidence: 99%
“…The need for thyroid hormone at and after birth is well established: routine neonatal screening can identify infants with thyroid deficiencies, and very importantly this information allows treatment with replacement hormone in time to reduce subsequent neurological impairment. In countries with the resources for comprehensive screening, congenital hypothyroidism is detected in about 1 in 3500 newborns (1). Studies in animal models have identified a number of cellular migration and differentiation events in the postnatal brain that depend upon thyroid hormone (2).…”
mentioning
confidence: 99%
“…This requires normal development and function of the hypothalamic-pituitary-thyroid axis, as well as an adequate nutritional intake of iodine. In iodine sufficient regions, permanent congenital hypothyroidism affects about 1:3000 to 1:4000 newborns (1)(2)(3)(4). In about 85% of all cases, congenital hypothyroidism is associated with developmental defects that are referred to as thyroid dysgenesis.…”
mentioning
confidence: 99%
“…The exact molecular mechanisms responsible are not clearly known, but studies have demonstrated the mutations of regulatory genes encoding for transcription factors -PAX-8, TTF-1 and TTF-2, which are essential for thyroid morphogenesis and differentiation may be responsible for abnormal migration of the gland. (7,8) In all the case series and reviews on the ectopic thyroid reported so far, a marked female preponderance has been observed. (5,9,10) In our series also we found female-to-male ratio of 5:2.…”
Section: Discussionmentioning
confidence: 98%